Semantic Fields in Pro-Palestinian Resistance Omani Poetry: “Fathun Qarīb” Poetry Collection as an Example - Al-Buraiki, Hilal Bin Abdullah; Al- Zaabi, Talal Bin Ahmed (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to identify the semantic fields in the poetry collection Fathun Qarīb “A Close Opening” and investigate the artistic value of the simple utterances and structures that were employed in Omani poetry which supported the Palestinian resistance through conducting an in-depth analysis of some of poems of the poetry collection in question. Methods: The study used an analytical descriptive approach to explore the semantic fields in the poetry collection and unearth the fields and aspects which support the Palestinian resistance and analyze them in an endeavor to test the extent to which Omani poetry was earnest in supporting the resistance in Palestine. Results: The study results showed that Omani poets have succeeded to a large extent in employing the simple utterances and structures to support the Palestinian resistance in different military, religious, spatial, perilous and fragile semantic fields. This led to emphasize the artistic value of those fields. Conclusion: The study consolidates the notion that Omani poets have successfully reflected the essence of their poetry collection in the poems which the researchers investigated in this study. The poetry collection has also helped bring the Palestinian cause back to the surface of interest in Arabic, local and international occasions or events in an endeavor to raise the spirits of Arabs in the battlefield and internationally.